2003
DOI: 10.1007/s00221-003-1587-1
|View full text |Cite
|
Sign up to set email alerts
|

FMRI evidence for a 'parietal reach region' in the human brain

Abstract: Event-related functional magnetic resonance imaging was used to examine activation in the posterior parietal cortex when subjects made pointing movements or saccades to the same spatial location. One region, well positioned to be homologous to the monkey parietal reach region (PRR), responded preferentially during memory-delay trials in which the subject planned to point to a specific location as compared to trials in which the subject planned to make a saccade to that same location. We therefore conclude that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

50
252
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(303 citation statements)
references
References 25 publications
50
252
1
Order By: Relevance
“…Recent imaging results using saccade and pointing tasks also support this notion. Essentially every fMRI study conducted to date has reported either areas showing a saccade preference (Simon et al, 2002;Medendorp et al, 2005) or areas showing a pointing preference (Connolly et al, 2000;Astafiev et al, 2003;Connolly et al, 2003) but not a dissociation between two distinct networks with one selective for saccades and the other for reaching (although in some cases this may have been because establishing such a segregation was not the main goal of the paper and in others because the authors only looked for stronger activation for one effector). One positron emission tomography study reported an anatomical segregation for reaching and saccades (Kawashima et al, 1996), but the Talairach coordinates of the reach-related region (30, Ϫ35, 50) place it in a more anterior area, in the vicinity of primary somatosensory cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent imaging results using saccade and pointing tasks also support this notion. Essentially every fMRI study conducted to date has reported either areas showing a saccade preference (Simon et al, 2002;Medendorp et al, 2005) or areas showing a pointing preference (Connolly et al, 2000;Astafiev et al, 2003;Connolly et al, 2003) but not a dissociation between two distinct networks with one selective for saccades and the other for reaching (although in some cases this may have been because establishing such a segregation was not the main goal of the paper and in others because the authors only looked for stronger activation for one effector). One positron emission tomography study reported an anatomical segregation for reaching and saccades (Kawashima et al, 1996), but the Talairach coordinates of the reach-related region (30, Ϫ35, 50) place it in a more anterior area, in the vicinity of primary somatosensory cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Several existing imaging studies have taken advantage of this property in an effort to identify the human homologs of LIP and PRR by searching for task-specific or effector-specific areas in regions such as the intraparietal sulcus (IPS). However, the results of these studies have been hard to interpret with regard to the prevailing view that effector-specific modules populate the PPC (for review, see Grefkes and Fink, 2005;Culham and Valyear, 2006) (for examples, see Kawashima et al, 1996;Connolly et al, 2000;Simon et al, 2002;Astafiev et al, 2003;Connolly et al, 2003;Medendorp et al, 2003Medendorp et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Another strong case of functional specificity for a simple visual dimension is color (15), for which recent evidence from both fMRI and single-unit recording indicates the existence of multiple millimeter-sized color-selective "globs" in posterior inferotemporal cortex in macaques (16,17). Other brain regions have been reported to be selectively engaged in processing information about biological motion (18), visually guided reaching (19), and grasping (20). For most cases in the neuroimaging literature, however, the main claim is one of regional specificity (i.e., that the implicated function activates this region more than other brain regions) rather than of functional specificity (i.e., that the implicated region is more engaged for this function than other functions).…”
mentioning
confidence: 99%
“…MIP is active during reaching to targets, pointing, and arm movements (34)(35)(36). Other areas in the intraparietal sulcus are thought to mediate sensory-motor transformation for other effectors: the lateral intraparietal area (LIP) represents visual targets and saccades (19,24,37); the anterior intraparietal area (AIP) is active during hand grasping of 3D objects (38,39).…”
mentioning
confidence: 99%